PERANCANGAN ALAT PENGATUR SUHU AIR DAN PENGISIAN BAK AIR SECARA OTOMATIS MELALUI SHORT MESSAGE SERVICE BERBASIS MIKROKONTROLER - Syamsuddin, Eko; Wijono, FX. Sigit; Lesmana, Resto (TESLA Jurnal Teknik Elektro UNTAR, 2007)
Controlling water temperature and automatic filling water throught short message service using microcontroller being necessary. This system detects water level and temperature using high water limited sensor, temperature sensor, analog digital converter, interface, handphone, heater driver, and water pump driver. Microcontrolleras central of processing to active the system to make hot water and keep temperature, when get command message from handphone â€œSET HEATER ONâ€.